2017
DOI: 10.1017/s146342361700007x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in dementia diagnosis in England and association with general practice characteristics

Abstract: Objectives Improving dementia diagnosis rates in England has been a key strategic aim of the UK Government but the variation and low diagnosis rates are poorly understood. The aim of this study was to explore the variation in actual versus expected diagnosis of dementia across England, and how these variations were associated with general practice characteristics. Method A cross-sectional, ecological study design using secondary data source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…While we were able to link pollution exposures to the primary care record to obtain diagnoses of dementia, there are concerns around the variability of dementia diagnoses in UK primary care, 24 and a recent review has concluded that dementia diagnoses on primary care databases may not be an accurate reflection of the true prevalence. 25 Under-recording is thought to be a common issue, as the diagnosis is associated with a stigma for many, and GPs may be reluctant to diagnose dementia unless highly certain.…”
Section: Discussionmentioning
confidence: 99%
“…While we were able to link pollution exposures to the primary care record to obtain diagnoses of dementia, there are concerns around the variability of dementia diagnoses in UK primary care, 24 and a recent review has concluded that dementia diagnoses on primary care databases may not be an accurate reflection of the true prevalence. 25 Under-recording is thought to be a common issue, as the diagnosis is associated with a stigma for many, and GPs may be reluctant to diagnose dementia unless highly certain.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic accuracy and awareness of different symptoms may play a role in the association between the severity and nature of cognitive function and diagnosis; a meta-analysis of physician accuracy identified severity of dementia as the main predictor for accurate diagnosis. 48…”
Section: Severity and Nature Of Cognitive Impairmentmentioning
confidence: 99%
“…62 Evidence suggests that some GPs recognise and manage patients as having dementia without recording them in primary care record systems as having dementia. 19,48 It is possible that recent increases in the number of people diagnosed with dementia simply reflect an improvement in the coding of existing knowledge; further ongoing epidemiological studies such as CFAS and CADDY are needed to monitor this.…”
Section: Inpatient Hospital Visitsmentioning
confidence: 99%
“…Examples of the above scenarios are mental health conditions, such as anxiety and depression, stigmatized neurological conditions such as dementia, and chronic conditions which may have a "silent" onset, such as diabetes (18,19). Figures from a range of studies and two meta-analyses shown in Table 1, they show that estimated rates of under-diagnosis for dementia, depression and anxiety, average about 50% (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Further assessments of completeness of EHR data, such as the review by Chan et al (36), show that missingness of parameters such as blood pressure and smoking status can be as high as 38-51%, but are less likely to be missing in populations where these parameters are important for clinical care, such as a high risk cardiovascular disease cohort.…”
Section: Dimensions Of Health Information Quality In Electronic Healtmentioning
confidence: 99%